The need for health economic model guidelines in South Africa - Chantel Siriram; Roseanne Harris (South African Journal of Economic and Management Sciences)
There are currently no guidelines in South Africa for effective decision making towards improving the health status of the population and ensuring fair and equitable resource allocation. This is because of the absence of a local health technology assessment (HTA) body and/or standardised framework for such assessments. Guidelines exist globally; however shortcomings include that they fail to make explicit allowance for rationing of care because of the affordability constraints.